The Effectiveness of Ventilator-Associated Pneumonia Prevention Strategies Among Critical Care Nurses: A Systematic Review - Alruwail, Samiyah Obaylik; Orabi, Maha Hassan; Alruwaili, Rawan Jalis; Doush, Ahood Abduh; Alruwaili, Amnah Rayei; AlShangeti, Norah Ahmed; Alanazy, Sumayyah Ibrahim; Alrowili, Hessah Owayed; Hazaa, Ola Yahya E.; Albehadel, Kawthar Ali; Allehebi, Rasha; Allehebi, Ghadi; et al. (Journal of Posthumanism, 2024)
Background: Ventilator-associated pneumonia (VAP) remains a major clinical challenge in intensive care units (ICUs), contributing to increased morbidity, mortality, and healthcare costs among mechanically ventilated patients. Critical care nurses play a central role in preventing VAP through the implementation of evidence-based interventions; however, variations in knowledge, compliance, and organizational resources continue to influence practice outcomes. Understanding the effectiveness of these prevention strategies is essential for improving patient safety and strengthening nursing performance in critical care settings. Aim: This systematic review aimed to evaluate the effectiveness of VAP prevention strategies implemented by critical care nurses and to identify factors influencing compliance and patient outcomes. Method: A systematic search was conducted across PubMed, CINAHL, Scopus, ScienceDirect, and Google Scholar for studies published between 2021 and 2024. Ten primary studies met the eligibility criteria and were evaluated using the Joanna Briggs Institute (JBI) critical appraisal tools. A narrative synthesis approach was applied due to heterogeneity in study designs and outcome measures. Results: Three major themes emerged: effectiveness of VAP prevention bundles, nurse knowledge and compliance, and organizational influences on practice. Most studies demonstrated that consistent implementation of VAP bundles significantly reduced infection rates. Higher knowledge and training frequency were linked to improved adherence, while staffing shortages, heavy workloads, and limited institutional support were common barriers to implementation. Despite variations across settings, evidence consistently supported the critical role of nurse-driven interventions VAP prevention is most effective when evidence-based interventions are supported by ongoing education, adequate staffing, and strong organizational resources. Strengthening these components may enhance compliance and improve patient outcomes in ICU settings.